Knowledge regarding suicide among parents having adolescents in a community of Kathmandu district. - Silwal, Barsha (2021)
ABSTRACT: Adolescent is vulnerable period due to various physical, social, environmental, and biological changes. Suicide is the second leading cause of death among 15-29 year old globally. Fostering parental support could lead to positive outcomes for adolescents who are struggling with life stress and suicidal thoughts. The main objective of this study was to find out the knowledge regarding suicide among parents having adolescents. A descriptive cross sectional research design was adopted for the study and non-probability purposive sampling technique was used to select 104 parents of adolescents. Face to face interview was conducted using structured interview schedule to collect data. Data was entered in SPSS version 16.0 and analysis was done by descriptive (mean, frequency, percentage) and inferential (chi-square test) statistical method. The present study revealed that 41.3% of respondents had moderately adequate knowledge regarding suicide. Level of knowledge of the respondents regarding suicide was significantly associated with economic status (p=.01) and sources of information (p=.01). The study concludes that only one fourth of the parents have adequate knowledge regarding suicide. So, it is recommended that awareness program through mass media can be conducted to raise knowledge of parents regarding suicide focusing on warning signs of suicide.